PENERAPAN PROYEK BERBASIS TIM (TEAM-BASED PROJECT) DENGAN E-LEARNING DALAM KONTEKS PENDIDIKAN TINGGI : Implementation of Team-Based Projects with E-Learning in The Context of Higher Education - Nasir, Rahma; Hadjar, Ibnu; Ishariyadi, Ishariyadi (Aksioma, 2024)
Higher education today is increasingly shifting towards a more collaborative learning approach, where students are given the opportunity to develop team skills, problem solving, and application of knowledge in real-world situations. One method that supports this approach is a Team-Based Project which is integrated with e-learning technology. This study aims to explore the implementation of Team Based Projects with e-learning in a higher education context and its impact on student learning. The research method used in this study is Classroom Action Research (PTK) with two cycles. The research was conducted at a university involving two classes, each consisting of second semester students in two courses, namely the student development course and the teaching and learning course. During the cycle, students are grouped into project teams and given collaborative assignments relevant to their curriculum. The use of e-learning technologies, such as online learning platforms and online communication tools, supports group work and mentoring. The instruments used in this research include document analysis in the form of student project assignments. Preliminary results show that implementing Team-Based Projects with e-learning can improve collaborative skills, understanding of material. This study provides insight into the potential of combining these approaches in a higher education context to prepare students with relevant skills in an increasingly complex and collaborative world of work.